Corruption in Indonesian Sports: Legal and Ethical Challenges in Managing Sporting Events (Indonesian Sports Justice Review, 2024)
Corruption remains a pervasive issue in the management and organization of sporting events in Indonesia, undermining the integrity and fairness of the sector. This paper critically examines the legal and ethical challenges posed by corruption in Indonesian sports, with a focus on the misallocation of funds, match-fixing, and fraudulent practices in event management. Drawing on case studies of high-profile scandals in Indonesian football and other sports, as well as interviews with legal experts, sports administrators, and athletes, the paper analyzes the structural and systemic factors that enable corruption in the sports sector. It explores how these corrupt practices affect the development of sports, public trust, and the welfare of athletes. The study also assesses the effectiveness of current anti-corruption laws and sports governance frameworks in Indonesia. The paper concludes with policy recommendations aimed at strengthening transparency, accountability, and ethical governance in Indonesian sports organizations, advocating for stricter regulations, independent oversight, and cultural change within the sector.